Biological Finality in the Philosophy of Life and Organisms - Ramellini, Pietro (Alpha Omega, 2015)
Summary: This paper is focused on the concept of finality in the bio-philosophical study of life and organisms. After some methodological remarks, the definition of biological finality is addressed. There are, in fact, wide variations regarding the concept of finality in biology, alt-hough the notions of finality as function or terminus are the most widespread. Given the vast and independent literature on functions, this paper mainly focuses on finality as a terminus, that is, a state or condition a biological entity reaches, or has the possibility of reaching. For what concerns the content of this concept, biologists have stressed above all the importance of self-maintenance and reproduction. Then, various types of finality are classified. Finally, as to the ontological and epistemological value of the concept, it seems that in general biology there is a slight tendency in favour of its use. Key words: General biology, bio-philosophy, philosophy of the organism, biological organism, biological life, biological finality Sommario: L’articolo esamina il concetto di finalità nella biofilosofia della vita e dell’organismo. Dopo alcune annotazioni di carattere metodologico, viene affrontata la de-finizione della finalità biologica. Esiste un ampio spettro di concetti di finalità in biologia, tra cui i più diffusi sono la finalità come funzione e come termine. Poiché esiste un’ampia e in-dipendente letteratura sulle funzioni, l’articolo si concentra sul concetto di finalità come termine, cioè come qualcosa a cui un’entità biologica giunge, oppure ha la possibilità di giungere. Per quanto riguarda il contenuto di questo concetto, i biologi hanno sottolineato soprattutto l’automantenimento e la riproduzione. Segue una classificazione di diversi tipi di finalità. Quanto infine al valore ontologico ed epistemologico del concetto, sembra che nella biologia generale vi sia una leggera tendenza in favore del suo uso. Parole chiave: Biologia generale, biofilosofia, filosofia dell’organismo, organismo biologico, vita biologica, finalità biologica, teleologia biologica, funzione biologica.